Rapid amplification system for recombinant protein production in Chinese Hamster Ovary (CHO) Cells - Metta, M K; Kunaparaju, R K; Tantravahi, S (Cellular and Molecular Biology, 2016)
Recombinant therapeutic proteins have changed the face of modern medicine in the present trend and they continue to provide innovative therapies for deadly diseases. This study describes the development of a novel stable expression system for rapid amplification of genes in Chinese Hamster Ovary (CHO) cells. The expression system consists of a host CHO cell line and an expression vector (pUB-PyOri-D-C) which encodes for Polyomavirus (Py) Origin of Replication (PyOri) for amplification of integrated genes in the presence of Py Large T Antigen (PyLT) and Dihydrofolate Reductase (DHFR) selectable marker gene for selection in the presence of Methotrexate (MTX). Use of both PyOri/PyLT and DHFR can reduce the number of rounds of selection and amplification required for isolation of high producing clones. The efficiency of pUB-PyOri-D-C was compared with that of pUB-D-C plasmid using Green fluorescent protein (GFP) and Erythropoietin (EPO) as reporter proteins. Our results showed that pUB-PyOri-D-C-EPO can help development of high expressing clone in one round of selection/amplification as compared to multiple rounds of selection/amplification with pUB-D-C-EPO plasmid. CHO-DG44/EPO clone generated using pUB-PyOri-D-C-EPO gave a productivity of 119 mg/L in shake flask.